Solar-assisted synthesis of ZnO nanoparticles using lime juice: a green approach. (29th August 2017) - Hinge, Shruti P; Pandit, Aniruddha B
Abstract: Zinc oxide (ZnO) nanoparticles are those nanoparticles which have been synthesized in various morphologies and shapes. Their size and shape dependent properties and their applications in vivid sectors of science and technology make them interesting to synthesize. Present work reports a green method for ZnO nanoparticle synthesis using lime juice and sunlight. ZnO nanoparticles were also synthesized by conventionally used methods like heating, stirring or no heating and/or stirring. The nanoparticles were characterized using different techniques like UV–vis spectroscopy, scanning electron microscopy (SEM), x-ray diffraction (XRD) and dynamic light scattering (DLS). Thermo gravimetric analysis (TGA) was also carried out for the intermediate product to select the calcination temperature. Stoichiometric study reveals that the intermediate product formed is zinc citrate dihydrate. The synthesized calcined nanoparticles have good crystallinity, uniform shape, and high purity and were in the size range of 20–30 nm. These nanoparticles formed agglomerates of various shapes in the size range of 200–750 nm. This process is ecofriendly and is amiable for easy scale up.